The English Historical Review (JSTOR)
Tables of contents for recent issues of The English Historical Review are available at http://www3.oup.co.uk/enghis/contents/. Authorized users may be able to access the full text articles at this site. First published in 1886, The English Historical Review is the oldest journal of historical scholarship in the English-speaking world. It deals not only with British history, but with almost all aspects of European and world history since the classical era. It covers the history of the Americas, including the foreign policy of the USA and her role in the wider world (but excluding the domestic history of the USA since Independence).
Keywords: British Studies